Women Building and Rebuilding their Space on Muisne Island after the Earthquake of April 16, 2016 (2020)
This article relies on the story of an Afro-Ecuadorian female mollusk collector from Muisne Island. It explores the experience of surviving the 7.8 Richter scale earthquake of April 16, 2016, and the dynamics that gave way to building and rebuilding spaces. Within a theoretical framework combined with journalistic descriptions, it looks into the context before the natural disaster, which revealed poverty, violence, absence of institutions, and deficiencies in risk management by the state. In the particular case of Muisne women, gender inequalities became more acute in this convergence between previous abandonment, the disaster, and the new geopolitical landscapes of eviction. However, the disaster gave rise to strategies and processes of resistance and appropriation of spaces by women, which meant rethinking their living conditions.